Effects of hydrogen water and psychological treatment in a sample of women with panic disorder: a randomized and controlled clinical trial - Ana Belén Fernández-Serrano; Francisco José Moya-Faz; Cesar Augusto Giner Alegría; Juan Carlos Fernández Rodríguez; Jose Francisco Soriano Guilabert; Martín del Toro Mellado (Health Psychology Research)
Research suggests that inflammation is an important mediator in the pathophysiology of anxiety disorders. In addition, women are more likely to develop an anxiety and depression disorder, in comorbidity with a wide spectrum of diseases related to the immune system. In recent years, hydrogen-rich water has emerged as a promising therapeutic strategy to prevent and intervene in stress-related disorders, due to its antioxidant and anti-inflammatory properties. The present study aims to analyze the effects of psychological treatment and a hydrogen-rich drink on the severity of anxiety and depression, pro-inflammatory cytokine levels, the cortisol awakening response, and general health state in a sample of women with panic disorder. This is a completely randomized, placebo-controlled study. The treatment group simultaneously received psychological treatment and 1.5 L of hydrogenated water for three months, compared to the control group that received psychological treatment and placebo. The results show that the treatment group was not significantly better than the control group. But there was a further reduction in measured pro-inflammatory cytokine scores, improving body pain and physical health. When between-group treatment effects were removed, psychological treatment significantly decreased measured variables, including cytokines and cortisol. The results support the presence of a maladaptive inflammatory process in women with panic disorder.